The Influence of Various Types of Play on the Development of Coherent Monologue Speech in Children Aged 5-6 Years - Ekaterina S. Oshchepkova; Vera L. Sukhikh; Arina N. Shatskaya (RUDN Journal of Psychology and Pedagogics, 2023)
Coherent monologue speech is one of the main factors determining both school performance and social success of children. Therefore, problems related to methods and techniques for developing coherent monologue speech in children still remain relevant. It is often recommended to use various types of play activities (i.e., games) for this purpose. However, the question remains whether all of them have an equally positive impact on the development of coherent speech in such an aspect as its macrostructure (coherence, cohesion, semantic completeness, narrative structure). For this reason, the purpose of this study is to find out how different types of play affect the speech development in children of senior preschool age. According to our preliminary hypothesis, the development of semantic elements of a story is most influenced by role-playing games. Our study involved 220 preschoolers ( M = 60.84 months; SD = 4.14 months) who were randomly assigned to seven groups in which they either participated in a series of games of a certain type, or listened to additional stories, or were not exposed to experimental treatment at all. Before and after the exposure, the children made up stories based on a series of pictures. The resulting stories were evaluated in terms of their macrostructure. The groups were then compared in terms of the impact that different types of play interaction had on the development of the macrostructure of coherent speech. It was found that the best effect was shown by the role-playing games, and, first of all, ‘directed’ ones. These results allow a more reasonable approach to the use of games for the development of coherent monologue speech in children aged 5-6 years.